2017
DOI: 10.1093/sleep/zsx037
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances and Risk of Hospitalization and Inpatient Days Among Older Women

Abstract: and poorer sleep quality (OR = 1.33, 95% CI 1.07-1.65) were each associated with a higher age and site-adjusted odds of hospitalization; associations were attenuated after multivariable adjustment for traditional prognostic factors with the OR for reduced SE (OR = 1.60, 95% CI 1.08-2.38) and shorter TST (OR = 1.63, 95% CI 1.12-2.37) remaining significant. Among women who were hospitalized, greater WASO (rate ratio [RR] = 1.20, 95% CI 1.04-1.37) and poorer sleep quality (RR = 1.18, 95% CI 1.02-1.35) were each a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
3
3
Order By: Relevance
“…In contrast to our findings, two prospective studies 36,40 utilizing data from the Study of Osteoporotic Fractures (SOF) for community‐dwelling older women linked to Medicare claims data in the United States reported that experiencing sleep disturbances, poor quality sleep, and insomnia symptoms among women at baseline were not associated with the risk or length of hospitalization, 36,40 or risk of skilled nursing facility stay 36 within 3 years of follow‐up. Evidence from other cross‐sectional studies of general adult populations indicates the presence of associations between independent, or combinations of, insomnia symptoms, including difficulty initiating and maintaining sleep, early‐morning awakening, nonrestorative sleep, and daytime sleepiness, and a wide range of health care and long‐term health care services.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings, two prospective studies 36,40 utilizing data from the Study of Osteoporotic Fractures (SOF) for community‐dwelling older women linked to Medicare claims data in the United States reported that experiencing sleep disturbances, poor quality sleep, and insomnia symptoms among women at baseline were not associated with the risk or length of hospitalization, 36,40 or risk of skilled nursing facility stay 36 within 3 years of follow‐up. Evidence from other cross‐sectional studies of general adult populations indicates the presence of associations between independent, or combinations of, insomnia symptoms, including difficulty initiating and maintaining sleep, early‐morning awakening, nonrestorative sleep, and daytime sleepiness, and a wide range of health care and long‐term health care services.…”
Section: Discussioncontrasting
confidence: 99%
“…Further, those who experienced both symptoms had higher frequencies of ED visits and hospitalizations compared to those with none of the symptoms. 39 In contrast to our findings, two prospective studies 36,40 concluded that experiencing insomnia symptoms were associated with higher hospitalizations, 17,32,34 ED visits, 30,32 physician visits, 17,[28][29][30][31]34 home health care utilization, 32 prescription refill and overuse of medications such sleep, pain, and antidepressant drugs, 17,29,30 and over-thecounter medications use. 30 Our results have significant implications for national health care costs, although additional study is needed before policy changes could be warranted.…”
Section: Sensitivity Analysescontrasting
confidence: 99%
See 1 more Smart Citation
“…Further, those who experienced both symptoms had higher frequencies of ED visits and hospitalizations, compared to those with none of the symptoms. 36 In contrast to our ndings, two prospective studies 33,37 utilizing data from the Study of Osteoporotic Fractures (SOF) for community-dwelling older women linked to Medicare claims data in the US reported that experiencing sleep disturbances, poor quality sleep, and insomnia symptoms among women at baseline were not associated with the risk or length of hospitalization, 33,37 or risk of skilled nursing facility stay 33 within three years of follow-up. Those reported associations were mainly attenuated and deemed nonsigni cant after adjustments for their baseline confounding factors such as comorbid medical conditions, functional limitations, depression, and cognitive functioning status of the respondents.…”
Section: Discussioncontrasting
confidence: 74%
“…[25][26][27][28][29][30][31] Studies focusing on longitudinal associations between insomnia symptoms and HSU are scarce. Furthermore, to our knowledge, the limited number of prospective studies available todate [32][33][34][35][36][37] employed only static measures of insomnia symptoms, usually at baseline, and followed individuals for HSU without considering the dynamic, complex, and bidirectional nature of these evolving associations in the life-course of individuals. In examining associations between insomnia symptoms and adverse health outcomes or HSU, it is important to take a life-course approach because sleep re ects dynamic neurobehavioral processes that change with age and interacts bidirectionally with cognitive, physical, and behavioral health factors that often evolve over time.…”
Section: Introductionmentioning
confidence: 99%